2016
DOI: 10.18632/oncotarget.7246
|View full text |Cite
|
Sign up to set email alerts
|

EPH/ephrin profile and EPHB2 expression predicts patient survival in breast cancer

Abstract: The EPH and ephrins function as both receptor and ligands and the output on their complex signaling is currently investigated in cancer. Previous work shows that some EPH family members have clinical value in breast cancer, suggesting that this family could be a source of novel clinical targets. Here we quantified the mRNA expression levels of EPH receptors and their ligands, ephrins, in 65 node positive breast cancer samples by RT-PCR with TaqMan® Micro Fluidics Cards Microarray. Upon hierarchical clustering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 42 publications
(54 reference statements)
1
28
0
Order By: Relevance
“…Reduced expression of EPHB2 29 and PDLIM1 30 are reported to be indicators of poor prognosis of colorectal cancer. Both genes appear to exhibit tissue-specific effects, with upregulation of EPHB2 reported to be associated with poor breast cancer survival31 and elevated expression of PDLIM1 reported to promote metastatic processes in breast and glioma3233. C4BPA and NLRC3 , genes involved in immune processes, are reported to be dysregulated in pancreatic34 and colorectal cancer, respectively35.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced expression of EPHB2 29 and PDLIM1 30 are reported to be indicators of poor prognosis of colorectal cancer. Both genes appear to exhibit tissue-specific effects, with upregulation of EPHB2 reported to be associated with poor breast cancer survival31 and elevated expression of PDLIM1 reported to promote metastatic processes in breast and glioma3233. C4BPA and NLRC3 , genes involved in immune processes, are reported to be dysregulated in pancreatic34 and colorectal cancer, respectively35.…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies have reported a direct correlation between EPHB2 expression and numerous human malignancies, including NSCLC. EPHB2 activates bidirectional signaling cascades and its upregulation predicts poor survival in LUAD [86], CRC [87], breast cancer [88] and malignant mesothelioma [89]. One study indicated that EPHB2 enhances cellular growth, migration and invasion in CeCa by a competitive inhibition that counteracts the miR-204 effect on cell cycle arrest, Bax overexpression and PI3K/AKT signaling pathway deactivation via competitive inhibition [90].…”
Section: Discussionmentioning
confidence: 99%
“…(77,81) The Eph receptors/ephrins have also been implicated in tumourigenesis, progression and metastasis across a wide range of malignancies (Table 3). ( (83) Prostate cancer (84,85) Breast cancer (86,87) Melanoma (88) Glioblastoma (89,90) Gastric cancer (91) EphA3 Gastric cancer (92) Colorectal cancer (93) EphB2 Advanced cSCC (94) Glioblastoma (95)(96)(97) Cervical cancer (98) Breast cancer (99) EphB4 HNSCC (100) Non-small cell lung cancer (101) Breast cancer (99) Downregulated EphA1 NMSC (77) …”
Section: Galaninmentioning
confidence: 99%